Cardioprotective Effects of Tualang Honey: Amelioration of Cholesterol and Cardiac Enzymes Levels - Khalil, Md. Ibrahim; Tanvir, E. M.; Afroz, Rizwana; Sulaiman, Siti Amrah; Siew, Hua Gan (Hindawi Publishing Corporation, 2015)
The present study was designed to investigate the cardioprotective effects ofMalaysian Tualang honey against isoproterenol- (ISO-) induced myocardial infarction (MI) in rats by investigating changes in the levels of cardiac marker enzymes, cardiac troponin I (cTnI), triglycerides (TG), total cholesterol (TC), lipid peroxidation (LPO) products, and antioxidant defense system combined with histopathological examination.Male albinoWistar rats (n = 40) were pretreated orally with Tualang honey (3 g/kg/day) for 45 days. Subcutaneous injection of ISO (85mg/kg in saline) for two consecutive days caused a significant increase in serum cardiac marker enzymes (creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), and aspartate transaminase (AST)), cTnI, serum TC, and TG levels. In addition, ISO-induced myocardial injury was confirmed by a significant increase in heart lipid peroxidation (LPO) products (TBARS) and a significant decrease in antioxidant enzymes (SOD, GPx, GRx, and GST). Pretreatment of ischemic rats with Tualang honey conferred significant protective effects on all of the investigated biochemical parameters.The biochemical findings were further confirmed by histopathological examination in both Tualang-honey-pretreated and ISO-treated hearts. The present study demonstrates that Tualang honey confers cardioprotective effects on ISO-induced oxidative stress by contributing to endogenous antioxidant enzyme activity via inhibition of lipid peroxidation.